Contribuições da pesquisa em sala de aula para formação integral de egressos do ensino médio - Reginato, Aline Estivalet (2020)
The context of this investigation is classroom research on the perception of high school graduates and their contributions to comprehensive education. The question that guided the study was: how did classroom research, in the perception of high school graduates, contribute to their integral training? Thus, the objective was to understand the contributions of classroom research to the comprehensive training of students graduating from high school. The research approach was qualitative and its typing the case study. The participants were 10 graduates from a public school in southern Brazil. They were used as instruments for data collection, namely: i) questionnaires; ii) press conference; and iii) field diary. From the graduates 'perceptions about research activities carried out during the school period, it was possible to: i) identify the graduates' memories of classroom research activities; ii) to know the suggestions of the graduates to improve Science Teaching and classroom research; iii) evaluate the presence of research contributions in the current daily life of high school graduates. The material from these instruments was analyzed using Discursive Text Analysis. Three categories emerged at the end of the analytical process, namely: i) students' perceptions about research; ii) classroom research in students' daily lives; iii) the importance of Pibid and the Integrated Seminar for personal training. Each category collaborated to understand the contributions of classroom research to integral training. In such a way, as three main considerations, it is exposed: i) regarding the challenges of contemporary society, integral education is configured as an essential path to be followed by educational institutions; ii) the student who uses research in his daily life experiences challenging cognitive situations and iii) research activities contribute to student leadership. Finally, the aim is to contribute so that research activities can be developed in schools, being part of everyday school life, in order to offer Comprehensive Education with regard to science teaching.